Penerapan Model Explicit Instruction Dalam Pembelajaran Akuntansi Pada Program Studi Pendidikan Akuntansi FKIP UMSU - Uun Ahmad Saehu; Siti Rohani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
The purpose of this study is to improve student accounting learning outcomes through the Explicit Instruction learning model. The research method used is Experiment. The research sample is 31 students with the instrument used is a written test in the form of pre-test and post-test. From the results of data analysis, it is known that an increase in student learning outcomes that can be seen through the pre-test reached 58.1% as many as 18 people then increased to 87.1% as many as 27 people in the post test. Thus, it can be concluded that the Explicit Instruction learning model can improve student learning outcomes because it can motivate students and be active in classroom learning.